As canções e filmes como recursos codificadores e descodificadores no currículo da EJA - Viana, Kety (2011)
This paper aims at investigating, through a critical perspective and through an educational approach from Freire s liberating views, the possibilities of building a critical syllabus, specifically a syllabus proposal for the Education of Youth and Adults, fundamented on the epistemological, ethic and politic theories stated by Freire through music and movies such as codifiers and decodifiers of generating themes in the curriculum of the EJA. Therefore, the study is performed at CIEJA Santana-Tucuruvi, with a Literacy class in the Human Science area. The theoretical referential about education and syllabus relies on the study of critical tradition authors such as Apple, Goodson, Arroyo, Sacristán, Saul and Silva. The action research and the methodology adopted are fundamented on Thiollent and on the epistemological and methodological categories by Freire in order to check the critical rationality necessary on the proposal. The results focus on the concrete possibilities of a critical syllabus guided by the dialogical, participating, ethic and political principles. The limitations and problems faced on building a critical syllabus still exist such as the rigid organization of school time and space, lack of group work among the educators making it difficult to perform interdisciplinary work and the lack of investment in the critical education of teachers